Collaborative Quality Improvement Strategy in Secondary Prevention of Cardiovascular Disease in India: Findings from a Multi-Stakeholder, Qualitative Study using Consolidated Framework for Implementation Research (CFIR). Issue 1 (11th October 2022) - Singh, Kavita; Huffman, Mark D.; Johnson, Leslie C. M.; Tandon, Nikhil; Prabhakaran, Dorairaj; Mendenhall, Emily
Background: Cardiovascular disease (CVD) is highly prevalent in India, and little is known about the perception of patients and providers about a package of collaborative quality improvement (C-QIP) strategies consisting of provider-focused electronic health records-decision support system (EHR-DSS), non-physician health workers (NPHW), and patient-facing text messages to enhance the CVD care. Objective: To explore the barriers and enablers of the C-QIP strategy from the perspective of providers, health administrators, patients, and care givers in India. Methods: We conducted a qualitative study using the consolidated framework for implementation research (CFIR) to understand the challenges and facilitators of implementing C-QIP strategy to enhance CVD care in the Indian context. A diverse sample of 38 physicians, 14 non-physician health workers (nurses, pharmacists), 4 health administrators, and 16 patients and their caregivers participated in semi-structured interviews. All interviews were audio-recorded, transcribed, translated, anonymised, and coded using MAXQDA software. We used the framework method and CFIR domains to analyze the qualitative data. Results: Barriers perceived from providers' and health administrators' perspectives in providing quality CVD care were high patient volume, physician burnout, lack of robust communication or referral system, paucity of electronic health records, lack of patient counsellors, polypharmacy, poor patient adherence to medications, and lack of financial incentives. Low health literacy, high cost of treatment, misinformation bias, and difficulty in maintaining lifestyle changes were barriers from patients' perspectives. The CFIR identified key enablers for the implementation of C-QIP such as standardized treatment protocol, reduced medication errors, improved physician-patient relationships, and enhanced patient self-care through trained and supported NPHW. Barriers included: heterogenous healthcare settings, diverse patient groups and comorbidities, associated costs of care and interoperability, confidentiality, and data privacy issues around the use of EHR-DSS. Conclusion: Strategies to enhance CVD care must be low-cost, culturally acceptable, and integrated into existing care pathways.